2006
DOI: 10.1002/jbm.a.30571
|View full text |Cite
|
Sign up to set email alerts
|

Development of a reinforced porcine elastin composite vascular scaffold

Abstract: Elastin, a principal structural component of native arteries, has distinct biological and mechanical advantages when used as a biomaterial; however, its low ultimate tensile strength has limited its use as an arterial conduit. We have developed a scaffold, consisting of a purified elastin tubular conduit strengthened with fibrin bonded layers of acellular small intestinal submucosa (aSIS) for potential use as a small diameter vascular graft. The addition of aSIS increased the ultimate tensile strength of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…it depicts an almost linear relation between the pressure and the radius. Interestingly, the pressure-radius response of the neo-Hookean model is compatible with a protective role of collagen and moreover consistent with experimental observations: Hinds et al (2006) tested purified elastin tubular conduits and observed a burst pressure of 162 AE 36 mmHg. Unfortunately, limited experimental data are available that depict the actual pressure-diameter response of purified arterial elastin tubes under inflation, this is due to the tendency of arterial elastinous tubes to form aneurysms and fail near physiological pressures (Lillie, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…it depicts an almost linear relation between the pressure and the radius. Interestingly, the pressure-radius response of the neo-Hookean model is compatible with a protective role of collagen and moreover consistent with experimental observations: Hinds et al (2006) tested purified elastin tubular conduits and observed a burst pressure of 162 AE 36 mmHg. Unfortunately, limited experimental data are available that depict the actual pressure-diameter response of purified arterial elastin tubes under inflation, this is due to the tendency of arterial elastinous tubes to form aneurysms and fail near physiological pressures (Lillie, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…Viscoelasticity is a mechanical feature which is necessary for inhibition of thrombosis and intimal hyperplasia in blood-contacting devices [62]. Viscoelasticity of biomaterials is largely depending on amount of elastin [63]. The AM has proper viscoelasticity to be employed in biomedical engineering [10].…”
Section: Evidencementioning
confidence: 99%
“…Other studies examine the use of SIS (Small Intestinal Submucosa), already amply employed in clinical management of wounds. These studies show the good mechanical properties of this biomaterial (Hinds MT et al 2006), but also the poor long-term patency of conduits (Pavcnik D et al 2009).…”
Section: Biological Materialsmentioning
confidence: 78%